Sources in the hybrid media system: coverage of inequality in the pandemic - Odriozola Chéné, Javier (2023)
The arrival of the Internet has involved a significant transformation of the media ecosystem. The legacy media have lost their monopoly on mass communication processes and have had to coexist with new media actors. In this context, the old and new logics of journalistic production coexist and interact in such a way that the old and new media adapt and co-evolve. The objective of this research is to show the effect of these changes in journalistic content in relation to the use of information sources and their identity and origin. For this purpose, a content analysis is carried out on a sample of 958 news contents developed by six Spanish online media during the first year of the pandemic to address the increase in inequality as a consequence of this crisis. The results reveal, on the one hand, how dynamics related to the new media ecosystem could limit the use of news sources and reduce the journalistic quality. Nevertheless, on the other hand, they also indicate how the greater importance given to social actors, who have not traditionally been the focus of media attention, contributes to the enhancement of news products.